2004
DOI: 10.1029/2003ja010335
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal and seasonal variations of quasiperiodic and periodic VLF emissions in the outer magnetosphere

Abstract: [1] We have analyzed ELF-VLF receiver and search coil magnetometer data from five Antarctic stations from 1998 and 1999 to study quasiperiodic emissions (QPs) and periodic emissions (PEs), which occur as ULF-range modulations of ELF-VLF signals between 0.5 kHz and $4 kHz. QPs are modulated at frequencies of $20-50 mHz, and PEs are modulated at frequencies of $200-500 mHz. The stations used covered a range of magnetic latitudes from À62°(Halley) to À74°(South Pole Station); three automated geophysical observato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 30 publications
8
49
0
Order By: Relevance
“…Later it was found both in space (on board the DEME-TER spacecraft) and on the ground at KAN (Bespalov et al, 2010). Earlier, the occurrence and seasonal variations of the similar short-period VLF emissions were studied by Engebretson et al (2004) based on the observations at Antarctic stations. They showed that their repetition periods were similar to the two-hop travel time of echoing whistlers and that the signal occurrence was strong in the local winter.…”
Section: Observationsmentioning
confidence: 99%
“…Later it was found both in space (on board the DEME-TER spacecraft) and on the ground at KAN (Bespalov et al, 2010). Earlier, the occurrence and seasonal variations of the similar short-period VLF emissions were studied by Engebretson et al (2004) based on the observations at Antarctic stations. They showed that their repetition periods were similar to the two-hop travel time of echoing whistlers and that the signal occurrence was strong in the local winter.…”
Section: Observationsmentioning
confidence: 99%
“…Omura et al [2009] have simulated the nonlinear generation of rising-tone chorus waves in the equatorial plane of the magnetosphere. QP emissions have been further categorized into emissions associated with geomagnetic pulsations (type 1) or not thus associated with them (type 2) [e.g., Sato et al, 1974;Sazhin and Hayakawa, 1994;Engebretson et al, 2004]. Pasmanik et al [2004] reproduced the amplitude/frequency modulation of type 2 QP emissions without geomagnetic pulsations by using a self-consistent set of equations from quasilinear plasma theory of energetic electrons and whistler wave spectral energy density.…”
Section: 1002/2014ja020161mentioning
confidence: 99%
“…VLF emissions having periodic or quasi-periodic structures with periods ranging from less than a second up to several minutes have been reported from mid and high latitude stations (Sazhin and Hayakawa, 1994;Engebretson et al, 2004). Periodic emissions with periods less than 10 s are divided into three main groups: periodic emissions, hisslers and pulsing hiss.…”
Section: Introductionmentioning
confidence: 96%